Student Teachers’ Practices: A Case of English Language Teaching Classrooms - Banstola, Pitri Raj; Corrie, Steve (Janapriya Journal of Interdisciplinary Studies, 2023)
The primary purpose of carrying out the study was to explore English language teaching (ELT) practices adopted by the student teachers (STs) in their classrooms and to examine the effectiveness of teaching practice (TP) of Janapriya Multiple Campus (JMC), Pokhara Nepal. The information was collected through unstructured tools such as observation, questionnaire, and focused group discussion (FGD). The collected information was analyzed through qualitative methods. The STs were found punctual, dedicated, and responsible in their TP. They were found practicing various classroom activities such as language games, role plays, discussions, group works, pair works, translations, question and answer, and drillings during their TP. In addition, they also were found conducting various activities in the classrooms such as debates, storytelling, essay writing, quiz contests, and eloquence. Moreover, they also carried out a case study and wrote a report, prepared a Secondary Education Examination (SEE) model question, constructed various types of questions, observed three peers’ classes, and kept a record of their classroom activities and teaching materials. Completing all the required activities, the STs performed effectively during their TP. The findings of the study can be useful to make the TP more effective.